Does the healthy vaccinee bias rule them all? Association of COVID-19 vaccination status and all-cause mortality from an analysis of data from 2.2 million individual health records - Fürst, Tomáš; Bazalová, Angelika; Fryčák, Tadeáš; Janošek, Jaroslav (International journal of infectious diseases, 2024)
OBJECTIVES: We investigated the validity of claims of the healthy vaccinee effect (HVE) in COVID-vaccine studies by analyzing associations between all-cause mortality (ACM) and COVID-19 vaccination status. METHODS: Approximately 2.2 million individual records from two Czech health insurance companies were retrospectively analyzed. Each age group was stratified according to the vaccination status (unvaccinated vs. individuals less than 4 weeks vs. more than 4 weeks from Doses 1, 2, 3, and 4 or more doses of vaccine). ACMs in these groups were computed and compared. RESULTS: Consistently over datasets and age categories, ACM was substantially lower in the vaccinated than unvaccinated groups regardless of the presence or absence of a wave of COVID-19 deaths. Moreover, the ACMs in groups more than 4 weeks from Doses 1, 2, or 3 were consistently several times higher than in those less than 4 weeks from the respective dose. HVE appears to be the only plausible explanation for this, which is further corroborated by a created mathematical model. CONCLUSIONS: In view of the presence of HVE, the baseline difference in the frailty of vaccinated and unvaccinated populations in periods without COVID-19 must be taken into account when estimating COVID-19 vaccine effectiveness from observational data.
Keywords: Retrospective Studies; Vaccination; retrospektivní studie; zdraví; Health; aklarubicin; COVID-19; Humans; lidé; vakcinace; vakcíny proti COVID-19; Aclarubicin; COVID-19 Vaccines